2018
DOI: 10.1021/acs.molpharmaceut.7b00715
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Pairing with Spermine Targets Theophylline To the Lungs via the Polyamine Transport System

Abstract: Certain xenobiotics, such as paraquat, are sequestered into the lungs from the systemic circulation by the polyamine transporter system (PTS). The aim of this study was to investigate whether ion-pairing a drug (theophylline) with a PTS substrate (spermine) provides a means of using this active transport mechanism to target drug delivery to the lungs. Fourier transform infrared spectroscopy showed that two of the amine groups of spermine interact with C-N and C═O of theophylline, leaving two free amines to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…The same problems were not experienced with the NMR data. [17] The affinity constants of the ion-pairs were consistent with previously reported estimates for ion-pairs formed with two hydrogen bonds (affinity constants of 0.8 [6] and 1.1 [7] ).…”
Section: Theophylline-cd Complex Characterizationsupporting
confidence: 90%
See 4 more Smart Citations
“…The same problems were not experienced with the NMR data. [17] The affinity constants of the ion-pairs were consistent with previously reported estimates for ion-pairs formed with two hydrogen bonds (affinity constants of 0.8 [6] and 1.1 [7] ).…”
Section: Theophylline-cd Complex Characterizationsupporting
confidence: 90%
“…The NMR data were in agreement with previous infrared spectroscopy studies, which also suggested the formation of 2 hydrogen bonds between theophylline and spermine. [6] The largest peak shift in the NMR spectra was observed for the theophylline C 8 -H peak and this was used to construct the theophylline-spermine association curve and derive the conditional association constant for the theophylline-spermine ionpair, pK NMR = 1.5 ± 0.02 (see Figure S1, Supporting Information). This conditional association constant was higher than the association constant generated by infrared spectroscopy, pK FTIR at 0.9 ± 0.1, reported in previous work.…”
Section: Theophylline-cd Complex Characterizationmentioning
confidence: 99%
See 3 more Smart Citations